Pragmatics: Some Basic Principles and Procedures - Adegbite, Wale (2014)
The importance of pragmatics to language studies is that it enables scholars and students to understand the principles and procedures guiding the interpretation of socio-cultural and contextual meanings of utterances. In this paper, we describe certain terms, principles and procedures of the pragmatics of language while exemplifying the discussion with some English utterances.